Implementation of Problem Based Learning Model to Improve Conceptual Understanding and Active Participation of Students in Zakat Learning in Elementary Schools - Kholid Asy'ari; Charlotte Cruz; Darnoto Darnoto (FITK UIN Walisongo Semarang, 2025)
This research is motivated by the low learning outcomes of students in zakat material in grade V of SD Negeri Bedono 1 Sayung Demak, which shows the need for the implementation of a more innovative and contextual learning model. The purpose of the study is to analyze efforts to improve student learning outcomes through the application of the Problem Based Learning (PBL) model to zakat materials in the classroom. This research uses a qualitative-quantitative approach in the form of Class Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 30 students (18 males and 12 females). Data were collected through observation, interviews, and learning outcome tests, then analyzed in a comparative descriptive manner. The results showed a significant increase in student learning outcomes: the percentage of learning completeness increased from 70% in cycle I to 90% in cycle II, with average test scores rising from 70 to 85. In addition, students' activities and enthusiasm during learning have also increased. These findings prove that the PBL model is effective in increasing students' conceptual understanding and active participation in zakat materials. This research makes a practical contribution to Islamic religious education in primary schools by offering relevant, contextual, and problem-solving oriented learning strategies